Древнерусские мужские отапеллятивные антропонимы, образованные путем парадигматической деривации - Hrynkiewicz-Adamskich, Bożena (Studia Rossica Posnaniensia, 2015)
Paradigmatic derivation is also referred to as conversion, zero derivation or zero affixation. It is a linguistic process that changes the paradigmatic features of an already existing word without using any affixes, which in some cases involves assigning that word to a new word class (a part of speech). This process concerns appellative lexis and proper names. The article is devoted to analyzing Old Russian male appellative anthroponyms that were formed in this way.